Implementasi Program Jaminan Kesehatan Nasional dalam Mencapai Universal Health Coverage (UHC) di Kabupaten Lombok Timur Study Tahun 2024 - Yuniar Affandy; Salmi Yuniar Bahri; Tuti Ika Ihwani (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2024)
Universal Health Coverage (UHC) is a health insurance system that ensures that every citizen in the population has fair access to quality promotive, preventive, curative, and rehabilitative health services at affordable costs. The achievement of Universal Health Coverage (UHC) planned in the National Medium-Term Development Plan (RPJMN 2020–2024), namely at least 98% of the total population becomes JKN members. The purpose of this study was to determine the Implementation of the National Health Insurance Program in achieving Universal Health Coverage (UHC) and the driving and inhibiting factors for the Implementation of the National Health Insurance Program in achieving Universal Health Coverage (UHC) which is specifically for the underprivileged in East Lombok Regency. This study uses a descriptive research type, using a qualitative approach. Based on the implementation approach, the four aspects that support the implementation of the program have been running well, but there are still some shortcomings in the communication aspect because there is still a lack of public awareness to realize that this program is indeed targeted at the underprivileged and have not received health insurance, resulting in inaccurate targets, and will actually become a burden on the government with the increase in the budget. The number of East Lombok residents who have JKN is 1,392,488 people (99.16%) of the total population of East Lombok Regency 1,404,343 people so that the UHC target of 98% has been achieved.